The expression that uses the product rule, which involves adding the exponents, is:
3^3 ⋅ 3^3
According to the product rule of exponents, when multiplying two expressions with the same base, you add the exponents:
3^3 ⋅ 3^3 = 3^(3+3) = 3^6.
Responses:
3^3 ⋅ 3^3
3^3 over 3^3
3^3+3^3
(3^3)^3
1 answer
The expression that uses the product rule, which involves adding the exponents, is:
3^3 ⋅ 3^3
According to the product rule of exponents, when multiplying two expressions with the same base, you add the exponents:
3^3 ⋅ 3^3 = 3^(3+3) = 3^6.